HLA-G and susceptibility to develop celiac disease. - Catamo, Eulalia; Zupin, Luisa; Segat, Ludovica; Celsi, Fulvio; Crovella, Sergio (Hum Immunol, 2015)
The Human Leukocyte Antigen-G has immunomodulatory function and its expression has been associated with several diseases. In our study we analyzed HLA-G polymorphisms in order to evaluate their possible association with susceptibility to celiac disease development. A total of 420 celiac patients and 509 controls were genotyped for HLA-G polymorphisms. We sequenced 800bp upstream the ATG codon (5' upstream regulatory region) and the whole 3' untranslated region of the HLA-G gene, whereas the ΔC deletion at exon 3 was detected by RFLP-PCR. Five polymorphisms (namely -477 C>G, -369 C>A, 14bp del/ins, 3187 A>G, 3196 C>G) and one haplotype (TCGGTACGAAITCCCGAG) were significantly more frequent in celiac patients than controls and associated with increased disease susceptibility. The 14bp I/I, 3187 G/G, 3196 G/G genotypes and TCGGTACGAAITCCCGAG haplotype, were still significantly associated with increased disease susceptibility (and in addition also the 3003 C/C genotype) when the analysis was restricted to patients and controls presenting the DQ2.5 or DQ8 HLA-DQ celiac disease risk haplotypes. Our findings indicate an association between HLA-G gene polymorphisms and susceptibility to celiac disease development, suggesting that HLA-G molecule is possibly involved in the pathogenesis of the disease.
Keywords: Adolescent; Adult; Alleles; Case-Control Studies; Celiac Disease; Child; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Genetic; Retrospective Studies